Sonological grading of non-alcoholic fatty liver and comparison with liver enzymes - Chaudhary, Arbind; Kafle, Pankaj; Karki, Lalit; Thapa, Narayan Bikram (Journal of Kathmandu Medical College, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is becoming more well acknowledged as a significant contributor to liver-related morbidity and mortality. Objectives: To assess the sonological grading of non-alcoholic fatty liver disease and comparison with liver enzymes. Methods: An analytical cross-sectional study was conducted from 2022 August to 2023 January among the patients referred to radiology unit for liver sonography with diagnosis of non-alcoholic liver disease. Ethical approval was obtained from the institutional review committee of Kathmandu Medical College (Ref. 12082022/06). A convenience sampling method was used. The sample size calculated was 107. Descriptive statistics (frequencies, means, and standard deviations) was used to describe the variables of interest. One-way analysis of variance was applied for comparison of serum liver enzymes in between various grades of NAFLD at 5% significance level. Results: Mean age of the patients was 37.9 ± 17.8 years, with 60% females. Most patients had grade I NAFLD (82, 76.6%), whereas 23 (21.5%) were of grade II. Levels of liver enzyme: Serum glutamic pyruvic transaminase (SGPT) with p-value 0.02 and serum glutamic oxaloacetic transaminase (SGOT) with p-value 0.03 were associated with fatty liver grade. Conclusion: Ultrasound-based grading of the severity of NAFLD was associated with abnormalities in the liver enzyme profile of patients. The SGPT and SGOT levels correlated with increasing severity of NAFLD based on ultrasound.